Machining and Phase Transformation Response of Room-Temperature Austenitic NiTi Shape Memory Alloy - KAYNAK, YUSUF (SPRINGER, 2014)
This experimental work reports the results of a study addressing tool wear, surface topography, and x-ray diffraction analysis for the finish cutting process of room-temperature austenitic NiTi alloy. Turning operation of NiTi alloy was conducted under dry, minimum quantity lubrication (MQL) and cryogenic cooling conditions at various cutting speeds. Findings revealed that cryogenic machining substantially reduced tool wear and improved surface topography and quality of the finished parts in comparison with the other two approaches. Phase transformation on the surface of work material was not observed after dry and MQL machining, but B19' martensite phase was found on the surface of cryogenically machined samples.
Keywords: cryogenic and MQL machining; phase transformation; room-temperature austenitic NiTi alloy; tool wear; XRD analysis; TOOL-WEAR; SURFACE INTEGRITY; DRY; BEHAVIOR; PERFORMANCE